Cases in emergency airway management - Berkow, Lauren C.; Sakles, John C. (Cambridge : Cambridge University Press, 2015)
Does your heart rate increase when you are paged to the emergency department or ICU for emergency airway management? Would you know how to handle the unexpected arrival of a patient with a gunshot wound to the neck and worsening airway compromise? This guide to critical airway emergencies will prepare you to safely manage these high-pressure situations. Case-based discussions focus on specific scenarios and provide background on the relevant medical issues along with practical guidance and algorithms. This systematic approach gives quick access to vital clinical information. Multidisciplinary in approach and written by experts from a variety of specialties, the content covers both pediatric and adult patients, encompassing many of the challenging airway situations you could be faced with. Every healthcare practitioner involved with emergency airway management will benefit from this book.
Title from publisher's bibliographic system (viewed on 13 May 2016).